Psychological Basis of the Formation of Рhilologists- Students’ Intellectual Competence in the Educational Process - Dauletbekova Ж.Т.; Yusup П.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
The article discusses ways of forming and developing the intellectual competence of students as a result of the educational process in higher education institutions. The features of intellectual identity as a category of psychological science and its importance in terms of learning outcomes are analyzed in detail. The public activity of the intellectual potential as a combination of knowledge and skills acquired by a specialist in a particular discipline, their professional achievements and a career in the workplace is considered on the basis of the work of researchers. Consideration of intellectual competence as an indicator of human intellectual development is the paradox of the fact that it is the real result of the acquired knowledge at university in the educational space. The article addresses these issues scientifically.